Logopedist role in childhood cerebral palsy – case report - Szpiech, Kamil; Gierszon, Patrycja; Łapiński, Rafał; Majewski, Artur; Kuś, Adrian; Markiewicz-Mazur, Oliwia (Journal of Education, Health and Sport, 2019)
This is a case study of a 5 years old girl, born as a premature child (27 weeks of pregnancy - extreme prematurity) with a very low birth weight and diagnosed with childhood cerebral palsy and drug-resistant epilepsy. In physical examination was shown: increased thoracic kyphosis, lopsidedness, contracted thoracic muscles, sciatica shin, hip-lumbar muscles, lower limbs in internal rotation. Girl should not be self-service and requires the help of a second person. She is circulatory efficient. She has also limb paresis, sensory disorders, perception, speech development disorders and eye damage.The girl has undergone logopedic therapy. Initially, the adaptation to the new environment and speech therapist was very hard. The observations, help in various situations and various games have made the therapy successful. During the therapy, it was noticed that the girl was sitting incorrectly. The parents also reported problems with acceptance of louder sounds and music (confirmed by the therapist and psychologist), which, however, improves during the therapy. Body motor skills in the described patient is very weak. Since the beginning of the therapy, a full logopedic examination was conducted and specialist tests were performed, which were evaluated on the basis of established scales. The girl is also under physiotherapist's care. The evaluation of the course of therapy shows the progress, and on the basis of the results of examinations and observations, a plan of further therapy has been prepared.